The relationship between the level of the occupational stress, organizational commitment (Affective), and job satisfaction with Organizational Citizenship Behavior (OCB) between genders in BERNAMA TV Synergy Sdn Bhd employees / Malini Md Kamal - Md Kamal, Malini (Faculty of Business and Management, 2010)
The Organizational Citizenship Behavior (OCB) is an important variable in to study of organization management. It’s a part to build relationship and performance within the organization. The purpose to create impression to the variable do to contribute significantly toward organization management. Compared with other organizational behavior present by the employees, OCB is the employees personal behavior that difficult to identify by the employer because it was the personally apply by the employer. Occupational stress (stressor), organizational commitment and job satisfaction are predictors variable to the Organizational Citizenship Behavior (OCB). All the variable useful to the organization to avoid the employees from making problems and if the variable not being apply, the company will be face by the comment employees problem such as low productivity and low performance. The employers should provide conducive working environment to reduce or to overcome the employee’s problem within the organization. Further, the findings show that only one component of organizational commitment-affective commitment-has a positive direct effect on OCB. In addition, the study indicates that occupational stress, organizational commitment (affective) and job satisfaction has relationship on OCB. According to Organ's (1988) definition, OCB represents "individual behavior that is discretionary, not directly or explicitly recognized by the formal reward system, and in the aggregate promotes the efficient and effective functioning of the organization".